Perceptions of Mental Health Conditions in Criminal Cases: A Survey Study Involving Swedish Lay Judges - Sörman, Karolina (Criminal justice and behavior, 2020)
Perceptions of mental health conditions influence how individuals with psychiatric diagnoses are treated within the community, in the legal system, and at different institutions. We examined perceptions of mental health conditions among lay judges (N = 643), working at district and appellate courts throughout Sweden. Participants read a web-based survey including a crime vignette in which the person charged with a crime was described as having schizophrenia (n = 186), antisocial personality disorder (ASPD) with psychopathic traits (n = 219), or intellectual disability (n = 238). Participants’ perceptions of schizophrenia were largely in line with Swedish legislation regarding the medicolegal concept of severe mental disturbance (SMD). Findings were more varied for the other two conditions, however. Perceptions of individuals with ASPD with psychopathic traits were not consistent with the Swedish SMD legislation. The results highlight the complexity of legislation addressing mental illness and criminality.